Circadian and wakefulness-sleep modulation of cognition in humans - Wright, Kenneth P.; Lowry, Christopher A.; LeBourgeois, Monique K. (Frontiers in Molecular Neuroscience, 2012)
Cognitive and affective processes vary over the course of the 24 hour day. Time of day dependent changes in human cognition are modulated by an internal circadian timekeeping system with a near-24-hour period. The human circadian timekeeping system interacts with sleep-wakefulness regulatory processes to modulate brain arousal, neurocognitive and affective function. Brain arousal is regulated by ascending brain stem, basal forebrain and hypothalamic arousal systems and inhibition or disruption of these systems reduces brain arousal, impairs cognition, and promotes sleep. The internal circadian timekeeping system modulates cognition and affective function by projections from the master circadian clock, located in the hypothalamic suprachiasmatic nuclei, to arousal and sleep systems and via clock gene oscillations in brain tissues. Understanding the basic principles of circadian and wakefulness-sleep physiology can help to recognize how the circadian system modulates human cognition and influences learning, memory and emotion. Developmental changes in sleep and circadian processes and circadian misalignment in circadian rhythm sleep disorders have important implications for learning, memory and emotion. Overall, when wakefulness occurs at appropriate internal biological times, circadian clockwork benefits human cognitive and emotion function throughout the lifespan. Yet, when wakefulness occurs at inappropriate biological times because of environmental pressures (e.g., early school start times, long work hours that include work at night, shift work, jet lag) or because of circadian rhythm sleep disorders, the resulting misalignment between circadian and wakefulness-sleep physiology leads to impaired cognitive performance, learning, emotion, and safety.